Applicability of the equations of Freundlich and Langmuir to the adsorption of the azo dye procion scarlet on paramorphic colonies of Neurospora crassa. - Corso, C. R.; Marcanti, I.; Yamaoka, E. M. (My University, 1987)
Experiments on the adsorption of Procion Scarlet MX-G by normal hyphae and by paramorphic colonies of Neurospora crassa were performed at pH 2.5, 4.5 and 6.5 at 30 degrees C. The measured adsorption isotherms were evaluated by the Freundlich and Langmuir equations. The removal of dye was most effective at pH 2.5 and more dye was adsorbed per unit mass of cells in the paramorphic cultures than in the normal hyphae. The statistical tests showed Langmuir's equation to give a better fit to the adsorption data.
Keywords: azo compound; dye; adsorption; mathematics; metabolism; Neurospora; Neurospora crassa; Adsorption; Azo Compounds; Dyes; Mathematics; Support, Non-U.S. Gov't